2022
DOI: 10.1038/s41598-022-15540-9
|View full text |Cite
|
Sign up to set email alerts
|

Planar, wide-band omnidirectional retroreflector using metal-only transmitarray structure for TE and TM polarizations

Abstract: In this paper, a novel planar and wideband metal-only retroreflector is proposed that efficiently reflects the obliquely incident electromagnetic wave along its incident direction in omnidirectional angle range. The means of omnidirectional is the capability of retroreflectivity in all azimuth angles $$(\varphi_{i} )$$ ( φ i ) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This plot illustrates the RCS enhancement around the designed incident angle at all three frequencies. To provide a comprehensive understanding of the characteristics of our work, a comparison between our proposed retroreflector and references [8,15,16,17,18,19] is presented in Table 3. It can be observed that while our proposed retroreflector exhibits a higher maximum ripple in the monostatic RCS, it is a single-layer structure with a very small total thickness.…”
Section: B Wideband Retroreflectormentioning
confidence: 99%
See 1 more Smart Citation
“…This plot illustrates the RCS enhancement around the designed incident angle at all three frequencies. To provide a comprehensive understanding of the characteristics of our work, a comparison between our proposed retroreflector and references [8,15,16,17,18,19] is presented in Table 3. It can be observed that while our proposed retroreflector exhibits a higher maximum ripple in the monostatic RCS, it is a single-layer structure with a very small total thickness.…”
Section: B Wideband Retroreflectormentioning
confidence: 99%
“…They proposed a planar monolithic near-infrared retroreflector composed of two layers of silicon nanoposts, which, following the cat's eye theory, reflects light along its incident direction with a normal incidence efficiency of 78% and a large half-power field of view of 60°. Then this method was subsequently implemented in the field of acoustics [16] and microwave [17][18][19]. From the works conducted so far in the field of retroreflectivity using metasurfaces, it can be concluded that single-layer metasurfaces with low thickness have only been utilized for single-angle or discrete multiple-angle retroreflection.…”
Section: Introductionmentioning
confidence: 99%